Inheritance of spheroid body and plastid in the raphid diatom Epithemia (Bacillariophyta) during sexual reproduction - Kamakura, Shiho; Mann, David G.; Nakamura, Noriaki; Sato, Shinya (Phycologia (Oxford), 2021)
Diatoms belonging to the family Epithemiaceae have endosymbiont 'spheroid bodies', which have received attention as a model to provide new insights into the early stages of organelle evolution. Uniparental organelle inheritance, known in a wide range of sexually reproducing eukaryotes, is considered to be one of the key characteristics acquired during the evolution of an endosymbiont into an organelle. However, there has been no information about the inheritance of spheroid bodies. The aim of the present study was, therefore, to investigate the inheritance modes of the spheroid bodies and plastids in the isogamous diatom Epithemia gibba var. ventricosa, which we established to be heterothallic. We induced sexual reproduction of E. gibba var. ventricosa in culture, using sexually compatible mating strains that differed with respect to nucleotide polymorphisms in the spheroid body and the plastid genomes. The F1 strains were genotyped to reveal the parental origin of the spheroid bodies and plastids using parent-specific polymorphisms. The results suggested that inheritance of the spheroid bodies was uniparental (i.e. progeny have the spheroid body genome from either parent but not both) and random (i.e. with an unbiased ratio of parental origins), while that of the plastids was more complex, being predominantly uniparental but with a few biparental cases. This study is the first to report the inheritance pattern of the spheroid body and will contribute to better understand the evolutionary state of this organelle.